Research on Promotion Strategies and Guarantee Measures for Fuyang’s Red Tourism Culture - Zhan, Yue; Li, Ji (International Journal of Social Sciences and Public Administration, 2025)
Fuyang boasts rich red tourism resources, including revolutionary sites, thematic memorial halls, and martyrs’ cemeteries, which feature distinct regional characteristics and profound historical connotations. This paper summarizes the value embodiment of Fuyang’s red tourism culture, proposes promotion strategies for it, and explores relevant guarantee measures for strategy implementation, aiming to facilitate high-quality development of Fuyang’s red tourism culture and inject new vitality into regional economic and social development.